If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 252 + -7x = 38x + -22 Reorder the terms: 252 + -7x = -22 + 38x Solving 252 + -7x = -22 + 38x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-38x' to each side of the equation. 252 + -7x + -38x = -22 + 38x + -38x Combine like terms: -7x + -38x = -45x 252 + -45x = -22 + 38x + -38x Combine like terms: 38x + -38x = 0 252 + -45x = -22 + 0 252 + -45x = -22 Add '-252' to each side of the equation. 252 + -252 + -45x = -22 + -252 Combine like terms: 252 + -252 = 0 0 + -45x = -22 + -252 -45x = -22 + -252 Combine like terms: -22 + -252 = -274 -45x = -274 Divide each side by '-45'. x = 6.088888889 Simplifying x = 6.088888889
| 4x+3(38-x)=130 | | y-2.5=4 | | 11-12x+x^2=0 | | y-21/2=4 | | F(x)=x^2+4x | | 7y-1=2y+24 | | 9x+34=60+8x | | 2x+12=51-5x | | -48+4x+4x^2=0 | | 4x/5-x=x/15-20/3 | | 3(2a-5)=27 | | 4U^2+20UV+9V^2=0 | | (5/x-3x)-7=-(1/2) | | 7[x+a]=b | | 7x^3+42x^2+63x=0 | | n=m-3/7 | | 21/25x10/12x6/9 | | 9x+9=6x+67 | | a[x+b]=c | | 9x^4+26x^2=0 | | Y-5=21 | | X^2-16x-99=0 | | 16(x^2)y/24(x)(y^3) | | 3(4x-1)-10x=90 | | 11x^4-32=0 | | x(2x-7)+x(2x-2)=(4x+9)(x-4) | | x/8-16=24 | | 5=-3/y-8 | | x/2+7=19 | | 9x^3+18x^2-16x-32=0 | | 4x^2=14x+5 | | 18=2x+5 |